2020
DOI: 10.3390/coatings10040352
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characterization of Waterborne Epoxy Resin and Styrene–Butadiene Rubber Latex Composite Modified Asphalt Emulsion (WESAE)

Abstract: Neat asphalt emulsions have poor physicochemical properties. In order to endow neat asphalt emulsions with excellent physicochemical properties and broaden their application as pavement, this study adopted the composite modification method using waterborne epoxy resin (WER) and styrene–butadiene rubber (SBR) latex. Firstly, a waterborne-epoxy–SBR composite modified asphalt emulsions (WESAEs) with different amounts of WER were prepared, and the storage stability, workability, and residual properties were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Moreover, following the SDGs, an additional improvement was introduced in this academic year. Apart from the standardized design of the pavement structure, some new research about more sustainable materials or construction procedures in pavements was presented, including the reutilization of previous pavements to manufacture some layers in new pavements [48][49][50][51][52][53] or the introduction of waste materials in the production of some materials [54][55][56][57][58][59][60][61][62][63][64]. Hence, students had to choose one of the recently investigated materials or procedures to propose a more sustainable pavement structure.…”
Section: Transport Infrastructurementioning
confidence: 99%
“…Moreover, following the SDGs, an additional improvement was introduced in this academic year. Apart from the standardized design of the pavement structure, some new research about more sustainable materials or construction procedures in pavements was presented, including the reutilization of previous pavements to manufacture some layers in new pavements [48][49][50][51][52][53] or the introduction of waste materials in the production of some materials [54][55][56][57][58][59][60][61][62][63][64]. Hence, students had to choose one of the recently investigated materials or procedures to propose a more sustainable pavement structure.…”
Section: Transport Infrastructurementioning
confidence: 99%
“…Due to the special properties of epoxy asphalt mixtures, researchers have attempted to research general road applications [36,37]. The proportion of epoxy resin will directly affect epoxy asphalt's structure and mechanical performance [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many research works have also been carried out on waterborne epoxy resin (WER)-modified emulsified asphalt, especially in the aspects of fog seal layer and pavement interlayer. The WER can form a porous continuous structure in WE/A with a low content of 3-4% [9][10][11][12][13][14][15][16], which can benefit the high temperature resistance to deformation performance. It has also been shown that WER can effectively improve properties such as thermal stability and adhesion of emulsified asphalt [17][18][19].…”
Section: Introductionmentioning
confidence: 99%